2004
DOI: 10.1081/ceh-120030234
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effect of Regular Endurance Exercise Training on Blood Pressure and Quality of Life in Patients with Hypertension

Abstract: Regular aerobic exercise can reduce blood pressure and is recommended as part of the lifestyle modification to reduce high blood pressure and cardiovascular risk. Hypertension itself, or/and pharmacological treatment for hypertension is associated with adverse effects on some aspects of quality of life. This study was performed to evaluate the effects of regular endurance exercise training on quality of life and blood pressure. Patients with mild to moderate hypertension (systolic blood pressure 140-180 or dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
18

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 29 publications
3
66
0
18
Order By: Relevance
“…The majority of studies show that aerobic exercises are more effective in promoting PEH in comparison with resistance exercises. These values range from 2 to 17 and from 2 to 7 mm Hg for systolic and diastolic BP, respectively, in aerobic exercises [4,32]. For resistance exercises, most studies prove a reduction of 2-13 mm Hg for systolic BP and 2-7.9 mm Hg for diastolic BP [23,[32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies show that aerobic exercises are more effective in promoting PEH in comparison with resistance exercises. These values range from 2 to 17 and from 2 to 7 mm Hg for systolic and diastolic BP, respectively, in aerobic exercises [4,32]. For resistance exercises, most studies prove a reduction of 2-13 mm Hg for systolic BP and 2-7.9 mm Hg for diastolic BP [23,[32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…A training session is composed of free unstable exercises and owing to this peculiarity they are performed with light loads which can progress to heavier ones (but still low in relation to resistance exercises) [2]. Isometric contractions generate high request of the trunk musculature (abdominal, paraspinal, gluteus, and pelvis), the region where the foundations of the body are located, which consequently favours adequate postural control [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…When compare the effect of different exercise intensities, low intensity exercise was more effective in lowering blood pressure than was high intensity exercise [14].…”
Section: Discussionmentioning
confidence: 99%
“…Jen Chen et al [14] found the effect of regular endurance exercise training on blood pressure and quality of life in patients with hypertension and found that low to moderate intensity exercise is effective in lowering blood pressure. When compare the effect of different exercise intensities, low intensity exercise was more effective in lowering blood pressure than was high intensity exercise [14].…”
Section: Discussionmentioning
confidence: 99%
“…Assim, diversos estudos relatam uma redução da PA em animais e humanos submetidos ao exercício físico (KOKKINOS et al, 2001;WALLACE, 2003;TSAI et al, 2004;HORTA et al, 2005). Isto talvez se explique pela diminuição da resistência vascular periférica onde o sistema nervoso simpático e o sistema renina-angiotensina parecem estar envolvidos.…”
Section: Hipotrófico Eutrófico Hipertróficounclassified